2015
DOI: 10.1007/s40593-015-0057-9
|View full text |Cite
|
Sign up to set email alerts
|

From Design to Implementation to Practice a Learning by Teaching System: Betty’s Brain

Abstract: This paper presents an overview of 10 years of research with the Betty's Brain computer-based learning environment. We discuss the theoretical basis for Betty's Brain and the learning-by-teaching paradigm. We also highlight our key research findings, and discuss how these findings have shaped subsequent research. Throughout the course of this research, our goal has been to help students become effective and independent science learners. In general, our results have demonstrated that the learning by teaching pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(46 citation statements)
references
References 29 publications
0
46
0
Order By: Relevance
“…A teachable learning companion-Betty's Brain-has been shown to help learners consolidate their knowledge. 43 Based on education theories such as learning-by-teaching 44 and argumentative learning, 45 VLCs can help learners organize what they have learnt into coherent knowledge by facilitating discussion and seeding reflections. Interactions with VLCs can also generate learning behaviour data to facilitate learning skill analytics.…”
Section: Personalizing Learning Supportmentioning
confidence: 99%
“…A teachable learning companion-Betty's Brain-has been shown to help learners consolidate their knowledge. 43 Based on education theories such as learning-by-teaching 44 and argumentative learning, 45 VLCs can help learners organize what they have learnt into coherent knowledge by facilitating discussion and seeding reflections. Interactions with VLCs can also generate learning behaviour data to facilitate learning skill analytics.…”
Section: Personalizing Learning Supportmentioning
confidence: 99%
“…However, it was also found that some students lacked some of the pre‐requisite skills and their wider rationale, eg, about reasoning along causal chains, so as to learn about the specific causal relationships in the eco‐system to be modelled (Biswas, Segedy, & Bunchongchit, ). In order to improve the system's effectiveness, the introductory narrative was augmented to explain the nature of this reasoning and to make it clearer that this kind of reasoning would have many other applications.…”
Section: Screen‐level Pedagogy: Example Systemsmentioning
confidence: 99%
“…In the transfer test, the benefits of the guided learning became even more visible as the SRL students were able to transfer their metacognitive strategies to a new learning environment, where most of the scaffolds to aid the learning task were removed. (Leelawong & Biswas, 2008, p. 205) However, it was also found that some students lacked some of the pre-requisite skills and their wider rationale, eg, about reasoning along causal chains, so as to learn about the specific causal relationships in the eco-system to be modelled (Biswas, Segedy, & Bunchongchit, 2016). In order to improve the system's effectiveness, the introductory narrative was augmented to explain the nature of this reasoning and to make it clearer that this kind of reasoning would have many other applications.…”
Section: Learning By Teachingmentioning
confidence: 99%
“…For the researcher/designer, the behaviour of all of the other actors is available as data. The design process can take as a starting point the position of the teacher as the user of learning designs (Biswam, Segedy, & Bunchongchit, 2016) or it may include the behaviour of the teacher, for instance in feedback used to redesign courses (Morse, 2014). Almost as a self-evident matter, the researcher's behaviour is off-limits.…”
Section: Actionable Insight Translates Into Changing Student Behaviourmentioning
confidence: 99%